2018
DOI: 10.3389/fmicb.2018.02088
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3B Activity Is Prevalent in Urothelial Carcinoma Cells and Only Slightly Affected by LINE-1 Expression

Abstract: The most common mutational signature in urothelial carcinoma (UC), the most common type of urinary bladder cancer is assumed to be caused by the misdirected activity of APOBEC3 (A3) cytidine deaminases, especially A3A or A3B, which are known to normally restrict the propagation of exogenous viruses and endogenous retroelements such as LINE-1 (L1). The involvement of A3 proteins in urothelial carcinogenesis is unexpected because, to date, UC is thought to be caused by chemical carcinogens rather than viral acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“…Cell viability as an indicator of proliferation was determined by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, Sigma-Aldrich) assays as described [28]. One thousand cells per well were seeded in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell viability as an indicator of proliferation was determined by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, Sigma-Aldrich) assays as described [28]. One thousand cells per well were seeded in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblot analysis of whole cell extracts was performed as described [28]. Cells were lysed in radioimmunoprecipitation assay (RIPA)-buffer (150 mM NaCl, 1% Triton X-100, 0.5% deoxycholate, 1% Nonidet P-40, 0.1% SDS, 1 mM EDTA, 50 mM TRIS, pH 7.6), containing a protease inhibitor cocktail (10 µl/mL, #P-8340, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Decreased DNA methylation at L1 promoters is particularly prevalent in urothelial carcinoma (UC), the most common cancer of the urinary bladder, and is associated with increased overall expression of full-length L1 elements [ 16 , 17 , 18 ]. Moreover, differences in the extent of active and repressive histone modifications at full-length L1 (flL1) sequences globally corresponded to differences in the levels of L1 mRNA and ORF1p expression in UC cell lines [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Here, we defined the individual L1 elements that are activated and expressed in the UC cell line VM-Cub-1 with high overall L1 mRNA and ORF1p expression using a novel approach. We have previously shown that L1 expression in that cell line is functionally relevant contributing to cell proliferation and escape from senescence [ 18 ]. Since L1 ORF1p associates preferentially with full-length L1 transcripts [ 14 ], we precipitated ORF1p-associated RNA using a highly specific antibody against ORF1p that has become available recently [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although A3A and A3B are accepted as intrinsic mutators of cellular chromosomal DNA, analyzed in several cancer types 8,11,17 , debate still persists regarding the contribution of each enzyme in the accumulation of mutations paving the way for oncogenesis. While, it has been described that A3A and A3B could be enzymatically active in different cancers 18 , A3A is the more active of the two enzymes and as a consequence, only A3A can produce double stranded breaks (DSBs), at least in an experimental setting 6,7,19 . Editing frequencies of >0.5 can be found which is why the phenomenon is referred to as hyperediting or hypermutation 9 .…”
Section: Introductionmentioning
confidence: 99%